2018
DOI: 10.2147/cmar.s167874
|View full text |Cite
|
Sign up to set email alerts
|

AP-2α expression in papillary thyroid carcinoma predicts tumor progression and poor prognosis

Abstract: BackgroundThe activator protein (AP)-2α is involved in a wide variety of biologic processes in tumor. However, little is known about the role of AP-2α in human papillary thyroid carcinoma (PTC).MethodsThe immunohistochemical method was used to detect AP-2α expression in 63 PTC cases. Western blotting was carried out to assess the change in expression of certain proteins. The bioinformatics analysis of 496 PTC samples comes from The Cancer Genome Atlas (TCGA). The Gene Set Enrichment Analysis (GSEA) was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…ChIP results con rmed the prediction. AP-2α was found to be highly expressed in PTC tissues, and the high expression of AP-2α mRNA was signi cantly correlated with advanced tumor stage and shorter overall survival 43 . Knock-down of AP-2α inhibited proliferation in PTC cells.…”
Section: Discussionmentioning
confidence: 96%
“…ChIP results con rmed the prediction. AP-2α was found to be highly expressed in PTC tissues, and the high expression of AP-2α mRNA was signi cantly correlated with advanced tumor stage and shorter overall survival 43 . Knock-down of AP-2α inhibited proliferation in PTC cells.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, our data demonstrated that AP2α expression presents a high prognostic value for CC. Wu and Zhang (2018) [ 19 ] showed in papillary thyroid carcinoma (PTC) that AP2α overexpression was significantly associated with tumor stage, histologic type, and independently predicted shorter OS. Patients with TFAP2α overexpression had a shorter OS than AP2α down-expression, particularly in PTC patients with advanced tumor stages (III and IV).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both AP-2α and AP-2γ have prognostic value for some tumor types. AP-2α overexpression is recognized as a prognostic indicator of shorter patient survival in papillary thyroid carcinoma and epithelial ovarian cancer but longer survival in gastric adenocarcinoma [20][21][22]. In terms of AP-2γ, its overexpression was also associated with poorer overall survival in breast cancer patients [23] with the other literature data to support this statement and enrich it with correlation presenting worse anti-hormone therapy response [24].…”
Section: Introductionmentioning
confidence: 92%